1993
DOI: 10.1093/hmg/2.12.2135
|View full text |Cite
|
Sign up to set email alerts
|

Missense mutations impair intracellular processing of fibrillin and microfibril assembly in Marfan syndrome

Abstract: Dermal fibroblasts from nine Marfan syndrome patients with missense mutations in the fibrillin-1 gene (FBN1) produced nearly normal amounts of fibrillin as determined by quantitative pulse-chase experiments. However, six of the seven mutations involving substitutions of highly conserved cysteine residues exhibited lower rates of intracellular transport and secretion. This effect is likely due to improper folding, since intracellular fibrillin processing was also affected by the reducing agent dithiothreitol. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 0 publications
5
40
0
1
Order By: Relevance
“…It was suggested that the delay in secretion might be due to targeted recognition of misfolded protein. In contrast, a smaller number of cases (24% of those studied) have been found in MFS patients with cysteine substitutions where normal secretion of fibrillin-1 has been observed (14,18). The C1977R substitution is one example where pulse-chase analysis of patient fibroblasts harboring this mutation showed normal synthesis, secretion, and deposition of fibrillin-1 compared with normal fibroblasts (Ref.…”
Section: Estimation Of K D Values For High Affinity Ca 2ϩ -Binding Simentioning
confidence: 92%
“…It was suggested that the delay in secretion might be due to targeted recognition of misfolded protein. In contrast, a smaller number of cases (24% of those studied) have been found in MFS patients with cysteine substitutions where normal secretion of fibrillin-1 has been observed (14,18). The C1977R substitution is one example where pulse-chase analysis of patient fibroblasts harboring this mutation showed normal synthesis, secretion, and deposition of fibrillin-1 compared with normal fibroblasts (Ref.…”
Section: Estimation Of K D Values For High Affinity Ca 2ϩ -Binding Simentioning
confidence: 92%
“…Otherwise, transport of the mutant receptor through the endoplasmic reticulum (ER) may be reduced or slowed, as occurs for other proteins, the mutations of which recall those of CADASIL and which consequently have folding or protein aggregation problems in ER. In Marfan syndrome, for example the altered number of cysteines in EGF-repeats of fibrillin-1 causes accumulation of fibrillin in ER (Godfrey et al, 1990;Aoyama et al, 1993;Schrijver et al, 1999). Karlström et al (2002) observed that in their experimental system, the mutant receptor was more likely to form cell aggregates than the normal receptor.…”
Section: Do Cadasil Mutations Lead To Loss Of Receptor Function or Acmentioning
confidence: 99%
“…The disorder is inherited in an autosomal dominant fashion and is caused by mutations in a gene encoding a protein known to multimerize. In addition, a hallmark feature of classic MFS is severe deficiency of extracellular fibrillin, far below the amount predicted by a single functioning FBN1 allele ( 15,16). Finally, mutations causing very reduced levels of FBN1 mutant transcript have been associated with an extremely mild disease phenotype ( 17).…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylamide electrophoresis gels of cellular protein extracts after 35S-cysteine pulse and unlabeled-cysteine chase were evaluated by autoradiography and scanning densitometry as previously described (15). Calculated levels of fibrillin synthesis and deposition are presented in Table II.…”
Section: Introductionmentioning
confidence: 99%